ANTI-INFLAMMATORY ACTIVITY OF BAWANG DAYAK (ELEUTHERINE BULBOSA (MILL. URB.))ETHANOL BULB EXTRACTS - Paramita, Swandari; Nuryanto, Muhammad Khairul (Journal of Vocational Health Studies, 2018)
Background: Inflammation is a normal process in response to injury, but causes problems for the patient, including the appearance of pain, swelling, or fever. Anti-inflammatory agents generally used for those conditions, have several side effects to patients. Purpose: The objective of this research was to find alternative anti-inflammatory agents, especially from natural sources. Eleutherine bulbosa (Mill.) Urb. knew as "Bawang Dayak” belong to family Iridaceae is one of the natural sources for anti-inflammatory agents. This plant is known as traditional medicine in East Kalimantan and used as material in this research. Method: The experimental method of anti-inflammatory measurement using membrane stabilization activity for E. Bulbosa ethanol bulbs extracts. Result: The results showed that significant differences of EC50(p < 0.05) were achieved between indomethacin (26.39 ± 2.91) as the positive control with E. Bulbosa (52.87 ± 2.29). EC50 of E. bulbosa showed the potential anti-inflammatory activities with similar effectiveness to half indomethacin concentration. Conclusion: It could be concluded that E. bulbosa could be further developed as a new natural source of the anti-inflammatory agents.